Measuring the cost of continuous improvement in cancer care: A WA 'proof of concept' project - Smith, Claire; Millar, Lesley; Makate, Marshall (2020)
The goal of value-based healthcare (VBHC) is to focus on improving patient health outcomes within a resource constrained context. To understand value, both the processes that lead to optimal outcomes for patients and the cost of achieving these outcomes over the full care cycle must be determined. This analysis of key drivers of cost and patient outcomes over time is important so that patients receiving particular interventions who experience a variation in health trajectory or costs can be identified.